Measurement of the associated production of a single top quark and a Z boson in pp collisions at s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier, 2018)
A measurement is presented of the associated production of a single top quark and a Z boson. The study uses data from proton–proton collisions at √s = 13 TeV recorded by the CMS experiment, corresponding to an integrated luminosity of 35.9 fb−1. Using final states with three leptons (electrons or muons), the tZq production cross section is measured to be σ(pp → tZq → Wb+−q) = 123+33 −31(stat) +29 −23(syst) fb, where stands for electrons, muons, or τ leptons, with observed and expected significances of 3.7 and 3.1 standard deviations, respectively